ONLINE LEARNING SURVEY OF PUBLIC HEALTH STUDENTS IN A HEALTH SCIENCES FACULTY - Wicaksono, Arif (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Coronavirus Disease 2019 (COVID-19) pandemic had an impact on all sectors including the education sector. The world of conventional education that prioritizes offline learning in one class was required to turn into offline learning through information technology in order to prevent the transmission of COVID-19 disease. Relatively new online learning process in Indonesia will have a real impact on educational institutions and students.Aims: This survey aimed to find out the characteristics of students, perceptions of online learning, the effectiveness of online learning, and the obstacles found when online learning from the student’s side.Case description: The survey was conducted using a list of questions in the google form filled out by students of the Universitas X Pontianak which were taking Basic Biomedical 2 online course in the second semester of the academic year 2019/2020 in May 2020. A total of 30 students were participated in the survey. Respondents get the most internet access from mobile phone quotas and only 20% of respondents get good internet access conditions. Twenty-six point sixty-seven percent of respondents agreed with online learning and 10 percent of respondents said online learning was effective. internet signal conditions, difficulty understanding the material, too much assignment, and insufficient time are obstacles obtained when learning online. Conclusion: Education institutions and stakeholders should always conduct evaluations, improvements, and updates for facilities and human resources involved in online learning.